2009
DOI: 10.1007/s10798-009-9088-6
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual property: what do teachers and students know?

Abstract: As society changes from an industrial to a knowledge era increasing importance and value is being placed on intellectual property rights. Technology teachers need to have pedagogical content knowledge of intellectual property if they are to incorporate it into their learning programmes to enable students to consider how to respect others' intellectual property rights, how to protect their own ideas and how they can legitimately make use of others' intellectual property. A survey of technology teachers and a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…It was found that the participants were unable to explain the relevant IP law and there was confusion among registered patents, designs, and copyrights. The study recommended teachers’ learning programs by applying pedagogical content knowledge of IP (Starkey et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the participants were unable to explain the relevant IP law and there was confusion among registered patents, designs, and copyrights. The study recommended teachers’ learning programs by applying pedagogical content knowledge of IP (Starkey et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…One such research, its results published in 2009, relied on the answers of the lecturers of technical disciplines and a few students to determine their knowledge in intellectual property. e second part of this study explored the practical skills in intellectual property rights protection [29].…”
Section: Analysis Of Research and Publicationsmentioning
confidence: 99%
“…For example, patent files have been used as the learning materials in many engineering courses so that the students know how to protect their own ideas and legitimately use existing IP rules besides the way of innovation [2]. Indeed, the instructors need to have pedagogical content knowledge of IP rules if they are to incorporate them into their learning programs [12]. Offering the list of related patents to the students is not enough since the students are unable to gain the historical perspective on how designs have developed in this particular technical field.…”
Section: Theoretical Underpinning and Pedagogical Basismentioning
confidence: 99%